PENGARUH BIMBINGAN AKADEMIK DAN KEBIASAAN BELAJAR TERHADAP INDEKS PRESTASI BELAJAR MAHASISWA STAIN JURAI SIWO METRO - Ali, Muhammad (P3M STAIN Jurai Siwo Metro, 2013)
Learning habit and academic guidance are believed asÂ supporting factors for the studentsâ grade point appendix. A good learning habit and an effective academic guidance lead to optimum studentâs grade point appendix. The combination of the two variables influences the studentsâ grade point appendix. This research, then, is conducted based on such assumption above. The problems of this research are: is there any influence of the academic guidance toward the studentsâ grade point appendix? Is there any influence of the learning habit toward the studentsâ grade point appendix? Is there any influence of the academic guidance and the learning habit toward the studentsâ grade point appendix? The objective of this research is to know the influence of the learning habit and the academic guidance toward the studentsâ grade point appendix of the seventh semester students of PAI of STAIN Jurai Siwo Metro. The sample of this research is 45 students of PAI of STAIN Jurai Siwo Metro. A questionnaire technique is used to collect the data on the learning habit and the academic guidance. Meanwhile, a documentation technique is used to gain the data on the historical background of STAIN Jurai Siwo Metro and the data on the seventh semester studentsâ grade point appendixes. In collecting the data on the academic guidance, the researcher uses interview technique. The results of the research show that the academic guidance influences the studentsâ grade point appendixes with the value ofÂ R = 0.193 and R2 = 0.037; and that the learning habit influences the studentsâ grade point appendixes with the value of R2 = 0.007. Furthermore, the academic guidance and the learning habit simultaneously influence the studentsâ grade point appendixes with the value of R2 = 0.053. The researcher, therefore, concludes that the academic guidance and the learning habit influence the seventh semester studentsâ grade point appendixes of PAI of STAIN Jurai Siwo Metro.Â Keywords: Influence, habit and academic guidance, and studentsâ grade point appendix.